PENGARUH KUALITAS SUMBER DAYA MANUSIA, BUDAYA ORGANISASI DAN PROFESIONALISME TERHADAP KINERJA KARYAWAN BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) BHAKTI SUMEKAR SUMENEP - jurnalmap map; Saptari Winedar; Nugroho Mawardi Wibowo; Muninghar ÔÇì (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2019)
ABSTRACT This research was conducted at the Sharia People's Financing Bank (BPRS) Bhakti Sumekar Sumenep with a total sample of 60 people (using the random sampling method). The purpose of this study are 1). To describe the quality of human resources, organizational culture and performance professionalism of the Employees of the Islamic People's Financing Bank (BPRS) Bhakti Sumekar Sumenep, 2). To find out and test whether the quality of human resources, organizational culture and professionalism have a simultaneous influence on the performance of the Employees of the Islamic People's Financing Bank (BPRS) Bhakti Sumekar Sumenep, 3). To find out and test whether the quality of human resources, organizational culture and professionalism partially influence the performance of the Employees of the Islamic People's Financing Bank (BPRS) Bhakti Sumekar Sumenep, 4). To find out and test which variables among the quality of human resources, organizational culture and professionalism that have a dominant influence on the performance of the Employees of the Islamic Rural Financing Bank (BPRS) Bhakti Sumekar Sumenep. Keywords: Quality Human Resources (X1), Organizational Culture (X2), Professionalism(X3), and Performance of Employees (Y)